2010
DOI: 10.1093/protein/gzq058
|View full text |Cite
|
Sign up to set email alerts
|

The effects of affinity and valency of an albumin-binding domain (ABD) on the half-life of a single-chain diabody-ABD fusion protein

Abstract: Fusion of small recombinant antibody fragments to an albumin-binding domain (ABD) from streptococcal protein G strongly extends their plasma half-life. This ABD binds with nanomolar affinity to human (HSA) and mouse serum albumin (MSA). It was speculated that an increase in albumin-binding affinity should lead to a further increase in half-life. In the present study, we analyzed the effects of affinity and valency of the ABD on the pharmacokinetic properties of a bispecific single-chain diabody (scDb), applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 30 publications
6
46
0
Order By: Relevance
“…The three Z FcRn -ABD-Z Taq fusion proteins and the control were injected into mice, and serum concentrations were measured at different time points. ABD fusion proteins have been shown to have a long circulation half-life caused by ABD binding to SA, followed by FcRn-mediated rescue from lysosomal degradation (25,26). In agreement with the previous results, the terminal half-life of Z Taq -ABD was ∼33 h. This half-life is also comparable to the half-life of MSA (35 h).…”
Section: Serum Circulation Half-life Extension By the Affibody Molecusupporting
confidence: 89%
“…The three Z FcRn -ABD-Z Taq fusion proteins and the control were injected into mice, and serum concentrations were measured at different time points. ABD fusion proteins have been shown to have a long circulation half-life caused by ABD binding to SA, followed by FcRn-mediated rescue from lysosomal degradation (25,26). In agreement with the previous results, the terminal half-life of Z Taq -ABD was ∼33 h. This half-life is also comparable to the half-life of MSA (35 h).…”
Section: Serum Circulation Half-life Extension By the Affibody Molecusupporting
confidence: 89%
“…One of these would be to couple the agent to polyethylene-glycol (PEG), a method used for half-life extension of other common drugs [91]. Another option would be to fuse the agent to fragments of human serum albumin (HSA) or albumin binding ab-fragments, and thereby improve the plasma half-life [92]. Finally, the BiTE format can be extended by adding a third ab-derived scFv binding site, thus generating a tandem single-chain triplebody.…”
Section: Recruiting T-cells Via Cd3mentioning
confidence: 99%
“…9 Nevertheless, several studies demonstrated that Fc fusion proteins have a shorter plasma half-life in mice than IgG molecules. 3,10,11 While differences in affinity for FcRn was proposed as a possible mechanism responsible for the shorter half-lives of Fc fusion proteins in humans, 3,12 others failed to find a correlation between affinity for FcRn and the serum half-life for a family of antibodies investigated in mice and humans. 13 Here, we generated various carcinoembryonic antigen (CEA)-targeted IgG-like fusion proteins and compared their biochemical and pharmacokinetic properties to a chimeric IgG1 molecule.…”
Section: Introductionmentioning
confidence: 99%